Investigation on yield stress and strain ageing of structural steels - Vodopivec, Franc (Kovine zlitine tehnologije, 1998)
Five steels with yield stress 265 to 1003 MPa and the microstructure of polygonal ferrite and pearlite, distorted and acikular ferrite as well as tempered martensite were investigated. By heat treated steels a better agreement was found between the empirical and the calculated yield stress. By steels with a microstructure of polygonal ferrite and pearlite mechanical properties are strongly changed by cold deformation and hardly affected by the following ageing annealing. Heat treated steels are virtually non propensive to strain ageing.
Keywords: jeklo; mehanske lastnosti; trdnost; mikrostruktura